2013
DOI: 10.1186/1471-2407-13-92
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in prostaglandin E2 metabolism in human colorectal cancer liver metastases

Abstract: BackgroundProstaglandin (PG) E2 plays a critical role in colorectal cancer (CRC) progression, including epithelial-mesenchymal transition (EMT). Activity of the rate-limiting enzyme for PGE2 catabolism (15-hydroxyprostaglandin dehydrogenase [15-PGDH]) is dependent on availability of NAD+. We tested the hypothesis that there is intra-tumoral variability in PGE2 content, as well as in levels and activity of 15-PGDH, in human CRC liver metastases (CRCLM). To understand possible underlying mechanisms, we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 50 publications
2
8
0
Order By: Relevance
“…Contrary to our speculation, however, PGE 2 did not induce EMT of human breast cancer (MCF-7) cells. It has been shown that the level of PGE 2 is different between the central and peripheral regions of colorectal cancer [22]. Similarly, the function of PGE 2 may also differ depending on its subcellular localization.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our speculation, however, PGE 2 did not induce EMT of human breast cancer (MCF-7) cells. It has been shown that the level of PGE 2 is different between the central and peripheral regions of colorectal cancer [22]. Similarly, the function of PGE 2 may also differ depending on its subcellular localization.…”
Section: Discussionmentioning
confidence: 99%
“…Both assays were performed using previously protocols published [ 26 ]. For PGE 2 , serum-free conditioned medium was collected from cells after overnight incubation, and PGE 2 levels were measured using a competitive immunoassay (Amersham Biosciences, UK), and normalised to total cellular protein content as measured by Bradford assay.…”
Section: Methodsmentioning
confidence: 99%
“…Following ethical approval (06/Q1206/180) we investigated HPGD expression in 350 primary invasive breast cancers, all of which, had been surgically resected and received adjuvant TAM, and were represented on tissue microarrays (TMAs) [24,29] . Tumour staining was achieved using previously described methods [24,26].…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…COX-1 is constitutively expressed in several tissues and is responsible for various physiological functions, whereas COX-2 is an inducible enzyme, originally found to be induced by growth factors and other stimuli (7). Previous studies have demonstrated the relevance of COX-2 in human cancer, including colorectal cancer, cholangiocarcinoma, liver cancer, esophageal carcinoma, gastric cancer and pancreatic cancer (8)(9)(10)(11)(12)(13). Determinants of cell invasion, including cell motility, adhesion to the extracellular matrix and the gelatinolytic activity of metalloproteinase, are also modulated in COX-2-positive pancreatic cancer cells (14).…”
Section: Introductionmentioning
confidence: 99%